Studies on Metal-ligand Vibrations in the Complexes of Dioxomolybdenum(VI) and Zirconium(IV) with Dibenzyl Sulphide and Dibenzyl Selenide - Pandey, R.N.; Sinha, S.K.; Singh, Sarita; Sharma, R.N. (Asian Journal of Chemistry, 2010)
The octahedral complexes of Zr(IV) and MoO2(VI) with dibenzyl sulphide (DBS) and dibenzyl selenide (DBSe) having general formula [Zr(NH3)5L]·nH2O and NH4[MoO2(OH)3L] (where L = DBS or DBSe) have been prepared and investigated. IR data indicate that liga. ds co-ordinate through sulphur or selenium atoms of the C–S or C–Se group respectively. vZr–N, vZr–S, vZr–Se, vMo–S, vMo–Se and vMo=O mode of vibrations have also been reasonably assigned in the far infrared region of the spectra of the complexes.